2012
DOI: 10.1016/j.jval.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Transmission Modeling: A Report of the ISPOR-SMDM Modeling Good Research Practices Task Force-5

Abstract: The transmissible nature of communicable diseases is what sets them apart from other diseases modeled by health economists. The probability of a susceptible individual becoming infected at any one point in time (the force of infection) is related to the number of infectious individuals in the population, will change over time, and will feed back into the future force of infection. These nonlinear interactions produce transmission dynamics that require specific consideration when modeling an intervention that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
252
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(255 citation statements)
references
References 59 publications
(84 reference statements)
0
252
0
3
Order By: Relevance
“…Modeling approach was found to be important with regard to cost-effectiveness results. Despite the recommendations of Quinn et al [13] and working groups on cost-effectiveness analyses of vaccines [40,47], only five studies used a dynamic transmission model. We found that dynamic models predicted a higher impact of QIV on influenza morbidity than static models, resulting in better cost-effectiveness outcomes.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Modeling approach was found to be important with regard to cost-effectiveness results. Despite the recommendations of Quinn et al [13] and working groups on cost-effectiveness analyses of vaccines [40,47], only five studies used a dynamic transmission model. We found that dynamic models predicted a higher impact of QIV on influenza morbidity than static models, resulting in better cost-effectiveness outcomes.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Compartmental models are another type of dynamic transmission models, which are frequently used in infectious disease modelling [38]. The compartments represent population pools, and transition between compartments is represented by differential equations [39].…”
Section: Agent-based Models Versus Compartmental Modelsmentioning
confidence: 99%
“…In particular, DES models allow explicit incorporation of resource constraints (which may result in delays if the resources are not available). It should be noted that both these techniques are being increasingly used for health technology assessment [19][20][21].…”
Section: Examples Of Resource Modelling At Individual Organisational mentioning
confidence: 99%